Criminal Justice Reform, Community Supervision and Social Work in Indonesia: Some Preliminary Observations - Gillies, David (Asean Social Work Journal, 2025)
Indonesia’s new criminal code is poised to expand non-custodial approaches to sentencing offenders. Enhanced use of alternatives to custody may help reduce Indonesia’s prison population, lower re-offending rates, and enable more supervision of offenders in the community. This review article draws on comparative experience of criminal justice reform and the role of international cooperation to illustrate the opportunities and challenges for implementation. It also briefly surveys linkages between social work education and criminal justice in Indonesia. There are five key observations. First, experience from other jurisdictions suggests that enabling laws are only the first step. The legal proliferation of community-based sentencing options is not by itself sufficient to shift criminal justice away from a focus on retribution towards increased emphasis on restorative justice and rehabilitation. Second, greater use of non-custodial approaches also requires public engagement, sustained political will, and a disciplined public policy focus with a regulatory framework, supporting institutions and predictable resources. Third, professional social work associations, training institutions, and social workers at the intersection of the state, the offender, and the community, have a key role to play in enabling the transition to a more humane approach to criminal justice. Fourth, Indonesian efforts to align with ASEAN regional standards for the integration of social work in the justice sector is a work still in progress. Finally, outreach to international partners and to neighbouring jurisdictions may be helpful to compare experiences, identify effective ways of working, and pilot new approaches.